Accelerated leukocyte telomere erosion in schizophrenia: Evidence from the present study and a meta-analysis. (August 2016) - Rao, Shuquan; Kota, Lakshmi Narayanan; Li, Zongchang; Yao, Yao; Tang, Jinsong; Mao, Canquan; Jain, Sanjeev; Xu, Yong; Xu, Qi
Abstract: Human telomeres consist of tandem nucleotide repeats (TTAGGG) and associated proteins, and telomere length (TL) is reduced progressively with cell division over the lifespan. Telomere erosion might be accelerated or prevented to varying degrees when exposure to serious medical illnesses. In previous studies, an association between TL decrease and schizophrenia has been extensively reported; however, the results remain largely controversial. To further investigate TL in schizophrenia patients and reconcile this controversy, we first measured leucocyte TL (LTL) in our samples (52 paranoid schizophrenia, 89 non-paranoid patients and 120 controls), and then conducted a comprehensive meta-analysis of the existing results of LTL in patients of schizophrenia compared to healthy subjects. Totally, 11 studies encompassing 1243 patients of schizophrenia and 1274 controls were included in the final meta-analysis model. In our samples, significant reduction of LTL in paranoid schizophrenia was observed compared to controls (F = 50.88, P < 0.001); whereas there was no significant difference in LTL between non-paranoid schizophrenia and controls (F = 0.842, P = 0.360). For meta-analysis, random-effects model showed significant LTL decrease in patients of schizophrenia when compared to controls (Z = 2.07, P = 0.039, SMD = −0.48, 95% CI = −0.94 to −0.03). Moreover, a marginal decrease in LTL was observed in medicated patients (Z = 1.92, P = 0.055, SMD = −0.58, 95% CI = −1.18–0.01) and those patients with poor response to antipsychotics (Z = 1.76, P = 0.078, SMD = −0.60, 95% CI = −1.27–0.07). In conclusion, we observed significant reduction of LTL in individuals with schizophrenia compared with controls. However, all the studies included in the meta-analysis were cross-sectional, and better controlled long-term studies are needed to replicate this result.